Parent Caregiver Self-Efficacy and Child Reactions to Pediatric Cancer Treatment Procedures. (January 2014) - Peterson, Amy M.; Harper, Felicity W. K.; Albrecht, Terrance L.; Taub, Jeffrey W.; Orom, Heather; Phipps, Sean; Penner, Louis A.
This study examined how parents' sense of self-efficacy specific to caregiving for their child during cancer treatment procedures affected children's distress and cooperation during procedures. Potential correlates of caregiver self-efficacy (ie, demographics, child clinical characteristics, parent dispositional attributes, and social support) were also examined. Participants were 119 children undergoing cancer treatment procedures and their parents. Parents' self-efficacy about 6 procedure-specific caregiver tasks was measured. Parents, children, nurses, and observers rated child distress and parents, nurses and observers rated child cooperation during procedures. Higher parent self-efficacy about keeping children calm during procedures predicted lower child distress and higher child cooperation during procedures. Parent dispositional attributes (eg, enduring positive mood, empathy) and social support predicted self-efficacy. Parent caregiver self-efficacy influences child distress and cooperation during procedures and is associated with certain parent attributes. Findings suggest the utility of identifying parents who would benefit from targeted interventions to increase self-efficacy about caregiving during treatment procedures.